Biology of the southern giant hornet, Vespa soror: nest architecture, morphological differences among castes, and the genetic structure of colonies - Mattila, Heather R.; Nguyen, Lien T.P.; Perrard, Adrien; Bain, Maggie; Otis, Gard W. (Frontiers in Insect Science, 2023)
Giant hornets in the genus Vespa are apex predators that are known throughout Asia for their exceptional size and devastating group attacks on social insect colonies. The giant hornets include Vespa mandarinia, a well-studied and widespread temperate species, and Vespa soror, a poorly known sister species that is limited to subtropical and tropical regions of Southeast Asia. Both species have been recently documented on the west coast of North America, raising urgent questions about their potential impact in novel ecosystems. To better understand the biology of V. soror, we describe the nest architecture, caste morphology, and genetic structure of colonies in Vietnam. Comparisons of colony metrics between the two giant hornet species suggest important differences that are likely a consequence of the relatively warmer climate in which V. soror occurs. Like V. mandarinia, V. soror constructs large, underground nests of partially enveloped horizontal combs. However, compared to temperate V. mandarinia colonies, the longer nesting period of subtropical V. soror colonies likely resulted in relatively larger colony sizes and nests by the end of their annual cycle. Vespa soror workers and gynes were larger than males, distinguishable based on wing shape and body size (total length and measures of six body parts), and equivalent in size to female castes of V. mandarinia. We genotyped colony members from three mature nests, which revealed that males and females were offspring of singly mated queens. Two colonies were monogynous, but one colony was comprised of two unrelated matrilines. Polygyny has not been observed for V. mandarinia, but is more common in tropical hornet species. Our study sheds light on essential details about the biology of an understudied species of giant hornet, whose populous colonies and long nesting period suggest the potential for substantial ecological impact wherever they occur.